Visualidades educacionais:imagem, cultura visual e trabalho pedagógico - PINTO, Carla Gioconda Alves (2008)
This study is focused on manifestations and meanings that Elementary School teachers construct about images they choose to work in their visual arts classes. Five teachers with more than two years of teaching professional experience in the public educational system of Goiânia, Goiás, were invited to participate in this investigation. Interactive interviews were developed with the participants in order to gather information, questions and ideas about motivations that guide their images choice for pedagogical practice in the classroom. Two sessions of focal group interviews complement the methodological procedures in order to register and discuss conceptions and opinions about image and cultural manifestations. As symbolic systems, image and culture are interweaved through practices, concepts and values, defining educational and ideological positioning and creating points of view and versions of social reality. Subject positioning, ideas, actions and affections are dimensions that reveal the way human beings relate to themselves and to the world around them.